1964
DOI: 10.1128/aem.12.6.492-495.1964
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Salmonellae in Dressed Broiler-Fryer Chickens1

Abstract: WOODBURN, MARGY (Purdue University, Lafayette, Ind.). Incidence of salmonellae in dressed broiler-fryer chickens. Appl. Microbiol. 12:492-495. 1964.-Salmonellae were isolated from 72 of 264 broiler-fryer type chickens that had been purchased in retail stores in the Lafayette, Ind., area in 1963. Meat from the tail area and giblet portions were used in sampling. Equal nuimbers of dressed whole and cut-up birds were positive for salmonellae. Thirteen different serotypes were identified, the more common being Sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1965
1965
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The initial microbial count greatly influences broiler shelf-life (Arafa and Chen 1977). Fresh broilers in retail outlets have an initial contamination level of lo4 to lo' microorganisms per cm2 (Walker and Ayers 1956;Woodburn 1964) and normally can only be stored for 1 or 2 days at 3-92 and still maintain their freshness (Mountney 1976). One concern of processors is control of spoilage organisms which produce off-odors and can cause consumer rejection (Miller er al.…”
Section: Introductionmentioning
confidence: 99%
“…The initial microbial count greatly influences broiler shelf-life (Arafa and Chen 1977). Fresh broilers in retail outlets have an initial contamination level of lo4 to lo' microorganisms per cm2 (Walker and Ayers 1956;Woodburn 1964) and normally can only be stored for 1 or 2 days at 3-92 and still maintain their freshness (Mountney 1976). One concern of processors is control of spoilage organisms which produce off-odors and can cause consumer rejection (Miller er al.…”
Section: Introductionmentioning
confidence: 99%
“…:4:10% of the total number isolated from nonhough her human sources in the U.S. in the first 11 months ifferent M. of 1967 (13). Woodburn (20), over a 1-year atter orga-period, found that 27% of the poultry in retail the 92.5% outlets was contaminated with Salmonella. rhether the Morris and Ayres (12) found that from 7 to 14% oup distinct of birds received by a processing plant were positive for Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…of the fresh birds that had not been treated with ch lort e t racy dine * Wilson et al, (1961) recovered Salmonellae from 17% of 525 market poultry samples, Woodbum (1964) isolated Salmonellae (13 serotypes) from 27% of 264 dressed fryer chickens.…”
Section: Presence Of Salmonellae On Poultry Meatmentioning
confidence: 99%